Brain cDNA clone for human cholinesterase. - McTiernan, C (1987)
A cDNA library from human basal ganglia was screened with oligonucleotide probes corresponding to portions of the amino acid sequence of human serum cholinesterase (EC 3.1.1.8). Five overlapping clones, representing 2.4 kilobases, were isolated. The sequenced cDNA contained 207 base pairs of coding sequence 5' to the amino terminus of the mature protein in which there were four ATG translation start sites in the same reading frame as the protein. Only the ATG coding for Met-(-28) lay within a favorable consensus sequence for functional initiators. There were 1722 base pairs of coding sequence corresponding to the protein found circulating in human serum. The amino acid sequence deduced from the cDNA exactly matched the 574 amino acid sequence of human serum cholinesterase, as previously determined by Edman degradation. Therefore, our clones represented cholinesterase (EC 3.1.1.8) rather than acetylcholinesterase (EC 3.1.1.7). It was concluded that the amino acid sequences of cholinesterase from two different tissues, human brain and human serum, were identical. Hybridization of genomic DNA blots suggested that a single gene, or very few genes, coded for cholinesterase.